## x 2 – 1 2 (12 – x) = 7x + 3(8 – x) – 8

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

Lorem ipsum dolor sit amet, consectetur adipiscing elit.Morbi adipiscing gravdio, sit amet suscipit risus ultrices eu.Fusce viverra neque at purus laoreet consequa.Vivamus vulputate posuere nisl quis consequat.

## Answers ( No )

x=18 hope this helps

x = -22/3 = -7.333

Step by step solution : Step 1 :Equation at the end of step 1 : x 1

(—-(—•(12-x)))-((7x+3•(8-x))-8) = 0

2 2

Step 2 : 1

Simplify —

2

Equation at the end of step 2 : x 1

(— – (— • (12 – x))) – (4x + 16) = 0

2 2

Step 3 :Equation at the end of step 3 : x (12 – x)

(— – ————————) – (4x + 16) = 0

2 2

Step 4 : x

Simplify —

2

Equation at the end of step 4 : x (12 – x)

(— – ————————) – (4x + 16) = 0

2 2

Step 5 :Adding fractions which have a common denominator :

5.1 Adding fractions which have a common denominator

Combine

the numerators together, put the sum or difference over the common

denominator then reduce to lowest terms if possible:

x – ((12-x)) 2x – 12

———————————— = ———————

2 2

Equation at the end of step 5 : (2x – 12)

————————— – (4x + 16) = 0

2